Smart Cities : Second International Conference, SmartCT 2017, Málaga, Spain, June 1416, 2017, proceedings /: Second International Conference, SmartCT 2017, Málaga, Spain, June 1416, 2017, proceedings. ([2017]) - Unknown
No abstract available